Kako raziskovati multimorbidnost v družinski medicini? - Petek Šter, Marija (Zdravstveno varstvo, 2009)
Background: Multimorbidity in family medicine is the rule rather than the exception, yet in Slovenia this health problem has not yet been adequately studied. The aim of this systematic literature review was to determine how theissue of multimorbidity has been explored and to identify questions that still need to be addressed. Methods: We consulted Medline for the original English-language scientific articles dealing with the population aged 19 and older, published until mid-August 2008. Key words "multimorbidity, comorbidity, chronic diseases" and "general practice, family medicine, family practice, family physician, primary health care", were used. We evaluated the appropriateness of the collected studies, and incorporated papers on multimorbidity in family medicine into our further analysis. Results: Researchin multimorbidity began in the 1990s, and the number of published studies has been increasing recently. Investigators mostly use quantitative non-interventional studies to determine the extent and importance of multimorbidity and its impact on the quality of life and health care. Qualitative methodology was only used in one research project investigating the attitude of multimorbid patients towards drug use. Conclusions: In order to meet the need for a holistic and patient-centred care, further research on the effectiveness of different approaches to different groups of comorbid patients will be required. The planning of appropriate effective approaches will have to take into consideration physicians'' and patients'' beliefs and attitudes, which need to be assessed by qualitative methods.
Keywords: družinska medicina; kronične bolezni; metodologija; multimorbidnost; raziskave